2012
DOI: 10.1016/s1001-0742(11)60789-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of land use, climate, topography and soil properties on regional soil organic carbon and total nitrogen in the Upstream Watershed of Miyun Reservoir, North China

Abstract: Soil organic carbon (SOC) and total nitrogen (TN) contents as well as their relationships with site characteristics are of profound importance in assessing current regional, continental and global soil C and N stocks and potentials for C sequestration and N conservation to offset anthropogenic emissions of greenhouse gases. This study investigated contents and distribution of SOC and TN under different land uses, and the quantitative relationships between SOC or TN and site characteristics in the Upstream Wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(57 citation statements)
references
References 32 publications
7
49
0
1
Order By: Relevance
“…A part of this high variability results from differences in the depth of soil sampling, commonly down to 50-100 cm [17,41,42], tree species and forest age [43]. Previous studies have indicated that the conversion from native forests to plantations decreased soil C stock [51]. Globally, land use change from native forests to plantations decreases SOC stock by about 13% [11].…”
Section: Land Use Change Reduced Soil Cmentioning
confidence: 99%
“…A part of this high variability results from differences in the depth of soil sampling, commonly down to 50-100 cm [17,41,42], tree species and forest age [43]. Previous studies have indicated that the conversion from native forests to plantations decreased soil C stock [51]. Globally, land use change from native forests to plantations decreases SOC stock by about 13% [11].…”
Section: Land Use Change Reduced Soil Cmentioning
confidence: 99%
“…However, SOC in the tropical moist deciduous forest of Mizoram was 147 Mg C•ha −1 [34] and at another site it was reported 104.3 Mg C ha −1 in top 1 m of soil [33]. In China [36], forest land use change at upper 40 cm soil profile led to 37.2% variability in SOC. Similar result was also reported from peninsular Spain [37], where land use change explains 33% of SOC variability under different land uses and concluded that the SOC in secondary forest was higher than the plantations.…”
Section: Effect Of Land Use On Socmentioning
confidence: 99%
“…In most plant growth conditions, soil nutrients show high spatial heterogeneity [3,4], which is a result of factors, including parent material, topography, vegetation, climate, and biological conditions [5,6,7]. Land use changes and agriculture also strongly influence soil nutrient concentrations [8,9].…”
Section: Introductionmentioning
confidence: 99%